Evaluating the utility of global versus local geospatial data for secondary cities - Davis, Danielle Brooke, author; Laituri, Melinda, advisor; Tulanowski, Beth, committee member; Galvin, Kathleen, committee member (Colorado State University. Libraries, 2019)
The 21st century is experiencing the emergence of the world's secondary cities as major urban growth areas. Secondary cities are regional hubs for commerce, logistics, services, and governance. They have populations ranging from under 300,000 to 5 million and are experiencing rapid, unplanned and informal growth patterns. Their dynamic growth means secondary cities are often data-poor and under-resourced, which impacts the ability of governments to target development efforts, respond to emergencies, and design sustainable futures. This research is a result of the Secondary Cities (2C) Initiative of the U.S. Department of State, Office of the Geographer and Global Issue. This initiative utilizes field-based participatory mapping for data generation to help secondary cities prepare for resilience, human security, and emergency preparedness. Geospatial data are key to the sustainable development of secondary cities for the future. Given the importance of geospatial data I explore two types of geospatial data for informed city planning: globally available data and locally collected data. First, I examine globally available data by assessing Sustainable Development Goal (SDG) Indicator 11.3.1, which compares land consumption rate to population growth rate, utilizing the recommended data. I apply SDG Indicator 11.3.1 to five 2C cities: Denpasar, Indonesia; Esmeraldas, Ecuador; Kharkiv, Ukraine; Medellín, Colombia; and Mekelle, Ethiopia. Second, I examine locally collected geospatial data of urban springs data collected in Kharkiv, Ukraine as a potable water source during a case of emergency. Specifically, these examinations utilize suitable data that are products of the 2C Initiative. The results revealed unexpected nuances of both data types that proved complimentary to each other.
Keywords: secondary cities; urban springs; sustainable development goals; geospatial data